Self-Efficacy as Key Mediator: How Knowledge Sharing and Internal Communication Boost Employee Performance: Kepercayaan Diri sebagai Mediator Utama: Bagaimana Berbagi Pengetahuan dan Komunikasi Internal Meningkatkan Kinerja Karyawan - Irsyad Robbani; Wahyu Maulana (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study aims to identify benchmarks for developing employee performance by examining the effects of knowledge sharing and internal communication on performance, as well as understanding the mediating role of self-efficacy in these relationships at PT Marinal Indoprima. Employing a quantitative approach, data were collected through Google Forms and interviews with 80 employees, determined using the Slovin formula from a total population of 369 employees. The collected data were processed using Smart-PLS software and analyzed through the SEM-PLS method, which allowed for the examination of complex relationships between multiple variables simultaneously. The findings reveal that employee performance is positively influenced by knowledge sharing, but not significantly affected by internal communication. Furthermore, the study demonstrates that self-efficacy mediates the relationship between knowledge sharing and performance, but does not mediate the relationship between internal communication and performance. Both knowledge sharing and internal communication were found to positively impact self-efficacy, and self-efficacy itself has a direct positive effect on performance. The results suggest that organizations should focus on enhancing knowledge sharing practices and fostering self-efficacy among employees to improve performance outcomes, while recognizing that internal communication alone may not directly drive performance improvements. Theoretically, this research contributes to the expansion of knowledge regarding performance escalation mechanisms in organizational settings and provides valuable insights into the complex interplay between communication practices, individual psychological factors, and performance outcomes in the context of Indonesian manufacturing companies.